Analisis Hubungan Tingkat Pengetahuan Dan Kesadaran Resistensi Antibiotik Di Masyarakat Kelurahan Kemiling Permai Bandar Lampung - Atmaja, Yorano; Samor, Vania Amanda; Primadiamanti, Annisa (Jurnal Ilmiah Wahana Pendidikan, 2024)
Excessive and inappropriate use of antibiotics can cause the body more susceptible to disease, which complicates treatment as pathogens develop resistance to antibiotics. The aim of this research is to see and describe how much knowledge and awareness the people of Kemiling Permai Village, Bandar Lampung have regarding the use of antibiotics Methods: The research was conducted cross-sectionally using a questionnaire adapted from the WHO multicountry survey with analytical descriptive analysis with the Statistical Product and Service Solutions (SPSS 22) instrument. Based on 100 respondents, ot the respondent were men (54%) with ages between 30 – 50 (49%), high school education (65%), ASN/Private employment (70%) and income of 2 – 4 million (54%) It was found that the community Kemiling Permai Subdistrict has a low level of knowledge of antibiotic use, (39%) and a good level of awareness of antibiotic use, (81%), which indicates a lack of knowledge of the good use of antibiotics and the need for dissemination of knowledge about antibiotic use. The results of the Chi-square analysis did not show a significant relationship between knowledge and awareness of the factors gender, age, education, employment, but there was a significant relationship between the income factor and knowledge and awareness with a p-value of P = 0.036 < 0,05 and P = 0.016 < 0,05 due to the economic level. low and medium will tend to buy antibiotics without prescription to save medical costs, so it can be concluded 39% of the people of Kemiling Permai Subdistrict, Bandar Lampung, own it high level of knowledge regarding antibiotic use and 61% have a low level of knowledge. 81% of the Village community Kemiling Permai Bandar Lampung has a high level of awareness related to antibiotic use and 19% had a high level of awareness low.